Deutsche Bank and its strategy change: What it means for the German financial system - Reinhard H. Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
In early July 2019, Christian Sewing, the CEO of Deutsche Bank, proclaimed a fundamental shift of the bank's strategy after finally obtaining the approval of the Supervisory Board, which the management seems to have requested for quite some time. The essential point of the reorientation is a deep cut into the bank's investment banking activities. At the same time, those parts of the bank's activity portfolio that had been the mainstay of Deutsche Bank's business 20 to 25 years ago, in particular lending to large and mid-sized German and European corporate clients, shall be strengthened in spite of a simultaneous reduction of the bank's staff by 18,000 FTEs over the next three years. The bank's CEO, who has only been in office since about one year, was reported to have called this shift of strategy a "return to the roots of Deutsche Bank" at the press conference at which it was announced, without, however, making it clear to which roots he was referring: those of some 40 years ago, when Deutsche Bank was essentially a Germany-focused commercial bank, or even those from the late 19th century, when the bank had been founded with the mission to become an international bank with a strong capital market-orientation. In any event, the press was impressed and keeps repeating these words, that deserve to be taken seriously and irrespective of their vagueness may be justified. If it were successfully implemented, this change of strategy would indeed be fundamental and imply undoing what Deutsche Bank's former management teams had aspired to do in the last 20 or 25 years. The newly announced strategy shift raises two questions. Can it be successful, and what does it mean for the bank itself and its shareholders, for its staff and for its clients? And what does it imply for the German financial system? This note focuses on the latter question. What makes it interesting is the fact that the last fundamental change of Deutsche Bank's strategy of two decades ago, which aimed at transforming Deutsche Bank from a Germany-centered commercial bank into a leading international investment bank, had a profound - and in my view clearly negative - effect on the entire German financial system.
urn:nbn:de:hebis:30:3-507407
Keywords: 330; German financial system; corporate governance; German banks